Effect of Contract Management Practices on Procurement Performance a Case of Nyarugenge District - Jolly , Kyarisiima (International Journal of Scientific Research and Management (IJSRM), 2022)
The objective of the study was to investigate the contract management practices on the procurement performance. Specifically, the study sought to; to establish the relationship between compliance to technical specifications and procurement performance at Nyarugenge District; to assess the influence of resources allocation & utilization on the procurement performance at Nyarugenge District and to examine the role of contract terms & conditions in enhancing procurement performance at Nyarugenge District. This study adopted a descriptive survey design. The target population for this study was 127 comprising both staff of Nyarugenge District head office and contractors. The study used a sample size of 105 and applied stratified and simple random sampling methods in generating the sample. The study used a primary data collected using a questionnaire. Statistical package for social sciences (SPSS) computer software for data analysis was used to conduct the data analysis task. The statistics generated included descriptive statistics and inferential statistics. The qualitative data generated from open ended questions were categorized in themes in accordance with research objectives and reported in narrative form along with quantitative presentation. A correlation model was used to test the significance of the influence of the independent variables on the dependent variable. It was notable that there existed a strong positive relationship between the independent variables and dependent variable. The studied variables were very significant therefore needed to be considered in any effort to boost procurement performance. Based on the study findings, the study concluded that procurement performance of Nyarugenge District was affected by contract management practices. Therefore, other factors affecting performance needed to be established. These may include the legal framework, and staff competency among others needs further investigation.Keywords: Contract management practices, Procurement Performance